Soil and climate factors affect the nutrient resorption characteristics of desert shrub roots in Xinjiang, China - Luo, Yan; Wei, Wenya; Wang, Yaxuan; Xue, Tianai; Du, Kaijuan (Frontiers in Plant Science, 2025)
IntroductionNutrient resorption is a vital nutrient utilization strategy in desert plants and is essential for understanding desert ecosystems and addressing climate change. Although the resorption characteristics in plants have been studied extensively, those of desert plant roots remain insufficiently explored.MethodsThis study investigated the concentrations of nitrogen, phosphorus, and potassium, as well as their resorption efficiencies, in 21 shrubs within a desert ecosystem in Xinjiang, Northwest China. Our study was designed to compare nutrient resorption efficiency patterns among shrub species and assess how the these patterns respond to variations in climatic conditions and edaphic properties.ResultsThe results indicated that nitrogen resorption efficiency (NRE), phosphorus resorption efficiency (PRE), and potassium resorption efficiency (KRE) for all plants were 29.14 ± 0.98%, 37.58 ± 0.92%, and 42.20 ± 0.93%, respectively. Among functional groups, angiosperms exhibited higher PRE (36.31 ± 1.00%) and KRE (41.85 ± 0.98%) than gymnosperms. C4 plants (44.88 ± 1.53%) had significantly higher KRE than C3 plants (40.85 ± 1.17%). Among different families, Tamaricaceae had significantly higher NRE (33.84 ± 2.07%) and PRE (46.23 ± 1.72%) compared to others, while Solanaceae had the lowest KRE (33.84 ± 2.07%). Plant nutrient resorption efficiency is regulated by multiple environmental factors. Specifically, soil total phosphorus (STP) and total potassium (STK) serve as the primary drivers of NRE, while electrical conductivity (EC) and aridity index (AI) play critical roles in modulating PRE. Climate factors exhibit distinct influences: AI shows positive correlations with PRE in C3 plants and with NRE in C4 plants. MAT negatively affects KRE in C4 plants, whereas MAP exerts a positive effect on it. Notably, Polygonaceae plants demonstrate unique response patterns: NRE is jointly regulated by MAP and MAT, PRE is predominantly influenced by MAT and AI, and KRE depends on the combined influence of MAP and AI.DiscussionOur research further explores the mechanisms of nutrient cycling in desert ecosystems by analyzing the root nutrient resorption strategies of desert plants. This provides theoretical support for understanding how plants in desert ecosystems efficiently utilize limited nutrient resources under extreme drought conditions.